Contextualizing private sector-based seed system development: The case of sorghum in Eastern Africa - Hambloch, Caroline; Kahwai, Jane; Mugonya, John (SAGE Publications, 2021)
Private sector-based seed system development remains a key development intervention in Sub-Saharan Africa. Seed system interventions promoting the adoption of improved varieties through the private sector generally follow a linear, market-oriented technological adoption logic. A qualitative case study of the sorghum seed system in Kenya, Uganda, and Tanzania demonstrates that this model may not be able to drive the broad-scale adoption of improved sorghum varieties and to generate significant benefits for small sorghum-farming households. The findings suggest that the agro-ecological, social, and political-economic contexts critically determine the role improved varieties and the private sector can play in rural development. Improved sorghum varieties promoted by both the public and private sectors may not suit the needs, preferences and contexts of farming households. Seed companies hold sorghum as an add-on in their portfolio, investing less resources and research into sorghum compared to more profitable crops such as vegetable and maize seeds. Significant political-economic obstacles exist that favor the support of cash crops such as maize and rice, limiting the growth and development of the private sector in the sorghum seed system. We conclude that future interventions should build on approaches that aim to develop more diverse channels of seed delivery in both the formal and informal seed systems, adopt a livelihoods perspective to evaluate the costs, benefits, and risks associated with the adoption of new technologies, and acknowledge that seed system interventions are only one out of a portfolio of interventions to generate rural development.